The Influence of Cultural Factors, Social Norms, and Social Support on the Spread of Infectious Diseases in Communities in Indonesia - Firdaus, Adhy; Anurogo, Dito; Yamtana, Yamtana; Hidayati, Nanda (West Science Social and Humanities Studies, 2023)
This research investigates the influence of cultural factors, social norms, and social support on the spread of infectious diseases in communities in Indonesia through a quantitative analysis. The structural equation model (SEM) employed in this study examines the complex interplay between these sociocultural elements and their impact on the transmission of infectious diseases. Results indicate significant positive associations between cultural factors and the spread of infectious diseases, social norms and disease transmission, and unexpectedly, social support and disease spread. These findings challenge conventional assumptions, emphasizing the need for nuanced and culturally sensitive public health interventions. The study contributes valuable insights to the understanding of infectious disease dynamics within diverse communities and informs targeted strategies for effective mitigation.